Edukasi Bantuan Hidup Dasar pada Keluarga Pasien Post-Percutaneous Coronary Intervention dengan Diagnosis STEMI Anterior: Studi Kasus: Basic Life Support Education for Families of Post-Percutaneous Coronary Intervention Patients with Anterior STEMI: A Case Study - Sutini, Sutini; Kartini, Kevin; Susilawati, Susilawati; Cakrahayat, Agus (Chakra Brahmanda Lentera Institute, 2026)
Death on Arrival (DOA) is a critical issue in emergency care, reflecting delays in early response, limited access to health services, and inadequate emergency preparedness at the community level. Patients who have undergone percutaneous coronary intervention (PCI), particularly those with a history of ST-elevation myocardial infarction (STEMI), remain at high risk for recurrent cardiac events, including sudden cardiac arrest. Limited family knowledge regarding basic life support (BLS) may contribute to delayed first aid and increased mortality. Therefore, this study aimed to improve BLS knowledge among families of post-PCI patients diagnosed with Anterior STEMI. This study employed a descriptive case study design conducted in the Merak Ward of Dr. M. Salamun Air Force Hospital from December 6 to December 8, 2025. The participant was the family of a post-PCI patient with a medical diagnosis of Anterior STEMI. Data were collected using basic life support standard operating procedures and structured observation sheets. The results indicated an improvement in the family’s knowledge of basic life support following the educational intervention. The family demonstrated better understanding and ability to recognize and respond to emergency situations related to cardiac and respiratory arrest. In conclusion, basic life support education effectively enhances the knowledge and preparedness of families of post-PCI patients. Improved family readiness may play a crucial role in early emergency response and potentially reduce the risk of Death on Arrival in patients with high-risk cardiac conditions.